Investigasi Sagging Metoda Parabola pada Saluran Transmisi Terhadap Parameter Temperatur pada Saluran 150 Kv pada Gardu Induk Cigereleng - YOSAN AGENG NUGROHO; WALUYO WALUYO (MIND (Multimedia Artificial Intelligent Networking Database) Journal, 2021)
AbstrakAndongan adalah bentangan kawat konduktor dari dua ujung titik terendah ditarik garis lurus konduktor tersebut sehingga terbentuk lengkungan kebawah, kekuatan tarik pada andongan berfungsi untuk menahan dari kedua ujung kawat konduktor yang dibentangkan. Besar suatu nilai andongan dapat dilihat dari temperature pada sekeliling saluran transmisi, sehingga siang hari panjang kawat konduktor akan sedikit memanjang diakibatkan sinar matahari, dan sebaliknya malam hari. Untuk mempermudah perhitungan dan analisis andongan dengan menggunakan metoda parabola pada saluran transmisi 150 Kv, dengan hasil perhitungan secara manual. Andongan dengan metoda parabola pada parameter temperature, temperatur 20oC besar andongan 0,0898%, pada temperature 70oC tinggi andongan 0,01186% turun ketika temperature 175oC andongan 0,1544%.Kata kunci: Andongan, temperatur, metoda parabola, gardu induk, saluran transmisi 150 Kv AbstractSagging is main the stretch of conductor wire from the two ends of the lowest point drawn by a straight line of the conductor so that a downward curve is formed, the tensile strength of sagging serves to hold from both ends of the stretched conductor wire the magnitude of a sagging value can be seen from the temperature around the transmission line, so that during the day the length of the conductor wire will be slightly elongated due to sunlight, and vice versa at night. The facilitate for calculation and analysis of the sagging used the parabolic method on a 150 Kv transmission line, with the results of calculations manually. Sagging with parabolic method at temperature parameters, temperature 20 oC large sagging of 0.0898%, at a temperature of 70 oC, the sagging height of 0.01186% decreases when the temperature is 175 oC sagging 0.1544%.Keywords: sagging, temperature, parabolic method, substation, 150 Kv transmission line